Ammonium persulfate-initiated graft copolymerization of methacrylamide onto chitosan: synthesis, characterization and optimization - Zetty Azalea Sutirman,; Mohd Marsin Sanagi,; Ahmedy Abu Naim,; Khairil Juhanni Abd Karim,; Wan Aini Wan Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ammonium persulfate (APS)-initiated grafting of methacrylamide (MAM) onto chitosan was successfully prepared for the first time by free radical mechanism. Both chitosan and chitosan-graft-poly(methacrylamide) (chitosan-g-PMAM) were characterized using Fourier transform infrared spectroscopy (FTIR), solid state 13C NMR, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). Important factors affecting graft copolymerization such as reaction time, temperature and concentrations of APS, MAM and chitosan were investigated and optimized to obtain maximum grafting parameters. The optimum values for grafting percentage and yield of graft copolymerization were achieved under the following conditions: chitosan (1 g), MAM (4 g), APS (0.6 g), time reaction (4 h) and temperature (70ºC).